A Quantitative-Qualitative Classification for Igneous Building Stones Based on Brazilian Tensile Strength: Application to the Stone Durability - Amin Jamshidi; Luís Sousa (Applied Sciences)
Building stones are among the most widely used construction materials in building. The Brazilian tensile strength (BTS) is a key indicator for evaluating the durability of building stone against deterioration processes. To date, no quantitative–qualitative classification for the BTS of building stones has been introduced in the literature. This poses a serious challenge for building engineers and architects in selecting the most durable building stone in terms of BTS. In the present study, a novel classification for igneous building stones based on BTS was proposed. In this classification, stones fall into the seven BTS classes: weak (BTS < 1.3 MPa), moderately weak (BTS 1.3–4.2 MPa), strong (BTS 4.2–10.1 MPa), very strong (BTS 10.1–19.3 MPa), and extremely strong (BTS > 19.3 MPa). The applicability of the BTS classification was confirmed using data published on the BTS values of the building stones subjected to deterioration processes. Based on data analysis, it was found that a stone classified into a BTS class with a higher strength can exhibit better quality in terms of its durability against deterioration processes. Consequently, BTS classification has significant advantages as an efficient and practical tool in selecting the most durable building stone for use in a building.